Yield Analysis of Intercropping Mustard and Basil in Farmer in Sub-District Paal Merah Jambi City - Francisca Manullang, Theresi; Dwinta Pebrianti, Herni; Yunita, Wilma (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2025)
Mustard is a type of seasonal vegetable crop. Mustard has high nutritional value and is needed by various groups. In the cultivation of mustard plants there are always obstacles, the obstacle is the presence of pests in mustard plants. One of the pests in mustard plants is Plutella xylostella. Control measures to suppress the attack of P. xylostella pests can be done with technical culture controls, one of which is planting mustard in intercropping with basil plants. The aim of the study was to determine the B/C ratio of mustard from technical culture pest control by intercropping mustard + basil in farmers in Paal Merah District, Jambi City. This research was conducted in Paal Merah District, Jambi City and Plant Pest Laboratory, Faculty of Agriculture, Jambi University. This research was conducted for ± 3 months starting in February to April 2024. This study was conducted by comparing two treatments, namely mustard cultivation with monoculture planting patterns and mustard cultivation with intercropping planting patterns. The results of observations obtained in the intercropping pattern of mustard + basil, basil contributed 44.55% of income.